Mechanical Properties Changes of Irradiated Thermoplastic Elastomer - Manas, David; Mizera, Ales; Manas, Miroslav; Ovsik, Martin; Hylova, Lenka; Sehnalek, Stanislav; Stoklasek, Pavel (Polymers, 2018)
Some polymers need a cross-linking agent for the controlled cross-linking process of polymers with a tendency to degradation during the radiation cross-linking process. While, on the other hand, other polymers do not need a cross-linking agent-predominantly there are cross-linking polymers. The Thermo-Plastic Elastomer (TPE) that was used belongs to this group of predominantly cross-linking polymers; however, this agent is added because of faster reaction times and smaller irradiation doses. Microindentation⁻tensile and tensile impact tests were carried out on a thermoplastic sample-with, and without, a cross-linking agent. Small changes were measured between these materials at low radiation doses, (up to 66 kGy); nevertheless, at higher doses, the influence of the cross-linking agent on the mechanical properties is significant.
Keywords: mechanical properties; micro-hardness testing; tensile test; thermoplastic elastomer; radiation cross-linking